Behaviour of Rectangular Footing Subjected to Gepseous Soil under Eccentricity-Inclined Loads (Iraqi Journal of Civil Engineering, 2017)
In this study the behavior of rectangular footing on gypeous soil was studied under inclined and eccentric loading. The experiments were performed using laboratory scale rectangular footing rested on soil taken from Tikrit University site in Salah Al Din province under 3 m depth which has a gypsum content of (50.48 %). The load test was performed on rectangular footing at eccentricity of (e/B= 0, 0.1, 0.2 and 0.3) and an angle of inclination of the load with the vertical ( i= 0°, 5°, 10°, 15°and 20°). The local specifications of the soil are measured (density, moisture, maximum density and optimum moisture content), it is found that that the vertical settlement, horizontal displacement, and base inclination increases with the increasing of eccentricity and inclination of load, the values of bearing capacity that getting in this study was less than of the previous theoretical studies when the load was vertical, and is given a good agreement when load was inclined and field density and moisture of soil. The values of bearing capacity was decreased when the load eccentricity increased because of the effective area became small. It is found that a high settlement occur in footing when a water (unsaturated with gypsum salts) diffuses through the soil, then gypsum become soluble thereby the soil resistance decreases because of rupturing of chemical bond between gypsum and soil.